Visible-Light-Induced Photocatalytic Activity in FeNbO4 Nanoparticles - Cho, In-Sun; Lee, Sangwook; Noh, Jun Hong; Choi, Geun Kyu; Jung, Hyun Suk; Kim, Dong Wan; Hong, Kug Sun (AMER CHEMICAL SOC, 2008)
A novel method was used to synthesize orthorhombic FeNbO4 nanoparticles by a hydrothermal process followed by calcination at 600 degrees C, and their optical, photoelectrochemical, and photocatalytic properties were investigated. The microstructural and local structural properties were characterized using X-ray diffraction, field-emission scanning electron microscopy, transmission electron microscopy (TEM), and Raman spectroscopy. The FeNbO4 particles obtained were composed of much smaller nanocrystal lines, with an average size of 10-20 nm, compared to particles prepared at 1000 degrees C through a conventional solid-state reaction method. Moreover, the optical band gap energy of the nanoparticles was estimated to be 1.93 eV from the UV-vis diffuse reflectance, and their flat-band potential in 1 M NaOH was -0.4 V (SCE). The X-ray photoelectron spectroscopy analysis revealed that the nanoparticles had fewer surface defects, such as oxygen vacancies, than the particles prepared by the solid-state reaction method. The FeNbO4 nanoparticles also exhibited a much higher photocatalytic activity for the degradation of rhodamine B dye solution under visible light irradiation (>420 nm). This higher photocatalytic activity of the FeNbO4 nanoparticles was attributed to their higher optical absorption ability and smaller particle size, as well as fewer surface defects.
Keywords: GAS-SENSITIVE RESISTORS; SURFACE-DEFECTS; OXYGEN; NO; ADSORPTION; MOSSBAUER; OXIDES; SIZE; DYE